Entidades de assistência social e a Política Nacional de Assistência Social: a experiência das entidades que compõem o COMAS da cidade de São Paulo - Nunes, Carlos Rogério de Carvalho (2010)
This work to refer to investigate and indentily the reprecussion of the National Politic of the Social Welfare Work of the 2004, in the Social Welfare Work s institutions and organizations that consists of the Comas of the São Paulo city, in the management from 2008 to 2010, from the social-welfare-work rights in the National Politic. Left from the study of the lawful mark of the Federal Constitution from the 1988 and Social Welfare Work s Organic Law from 1993. Like that approached the evolotion of the social right s in the Brazil and the constitution of the Social Welfare Work s National Council and anybody else Welfare Work s Council. Analised like that the São Paulo city, and it evolution in the history. Analised the Social Welfare Work s institutions and organizations the consistes of the São Paulo s Comas and the application of the social-welfare-work rights, in the PNAS/04, by them institutions